Male Investment in Schooling with Frictional Labour and Marriage Markets - Roberto Bonilla; Francis Kiraly (Center for Economic Studies and ifo Institute (CESifo), 2019)
We present an equilibrium model with inter-linked frictional labour and marriage markets. Women's flow value of being single is treated as given, and it captures returns from employment. Single unemployed men conduct a so-called constrained sequential job search, and can choose to improve their labour market returns as well as their marriage prospects by under-taking a costly ex-ante investment in schooling. We establish the existence of market equilibria where a fraction of men get educated, and show that this fraction decreases if women's labour market returns increase. We also examine the robustness of such equilibria.
Keywords: D83; I26; J12; J16; J31; 330; frictional markets; constrained search; male returns to education